Vitamin B12 deficiency and depression in elderly: cross-sectional study in Eastern Croatia (Journal of Health Sciences, 2014)
Introduction: Vitamin B12 deficiency occurs frequently among elderly patients and it has recently been connected with the occurrence of depressive symptoms in this population. The aim of this study was to determine the frequency of vitamin B12 deficiency among elderly patients from Eastern Croatia and to evaluate whether there is a connection between this deficiency and the occurrence of depressive symptoms among them.Methods: This cross-sectional study was conducted from April to June 2013, among 140 elderly patients from Vukovar-Srijem County (47.9%, 67/140 males and 52.1%, 73/140 females; mean age 71.0±6.7 years). The anonymous questionnaire was used to obtain demographic data, data regarding socio-economic status and personal history of diseases of study participants as well as data pertaining to the existence of depressive symptoms among them. The competitive immunoassay vitamin B12 kit was used to determine serum levels of vitamin B12.Results: Among all study participants there were 7.1% (10/140) of them with B12 deficiency and 70.0% (98/140) of them with the symptoms of depression. Depressive symptoms occurred in 100.0% (10/10) patients with the vitamin B12 deficiency and 67.7% (88/130) of patients without it.Conclusion: The study showed positive connection between the existence of depressive symptoms and vitamin B12 deficiency among elderly patients. This finding points to the need for frequent vitamin status evaluation in this age group and its consequent correction that could improve overall health of this population subgroup.